Carbon nanotubes for bone tissue osseointegration engineering: a review / Saiful Amri, Ammar Mohd Akhir and Norhasyimi Rahmat - Amri, Saiful; Mohd Akhir, Ammar; Rahmat, Norhasyimi (Universiti Teknologi MARA Shah Alam, 2022)
In bone tissue engineering, latest advancements have drastically improved the process of surgical healing by carbon nanotubes that have grown as biocompatible products to address bone damage or deficiencies. The latest reconstructive solutions related to the bone tissue engineering industry have several benefits, but still, some inconveniences continue to emerge. The integration of carbon nanotubes as a replacement medium for implantable bone tissue enhances dramatically the mechanical properties of different biomaterials to scaffold the damaged region, which imitates natural bone. Carbon nanotubes and bio-matters have been improved recently for bone tissue applications. This review aims to analyse the utilisation of carbon nanotubes as bio-composite in bone tissue by comparing the biophysical and chemical properties of carbon nanostructures and discussing the functionality in bone tissue regeneration and how it can be utilised in the future in Malaysia.